1976
DOI: 10.1051/animres:19760407
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation Des Principaux Éléments Minéraux Du Mais Ensilé Par Le Mouton en Croissance

Abstract: Centre national de Recherches zootechniques, I. N. R. A., ., 783-50 Jol l y C i l Josas RÉSUMÉ Des bilans minéraux (l', Ca, Mg, lv, Na) ont été effectues sur 6 agneaux de 2 S kg consommant seulement de l'ensilage de maïs (3 ,8 g de Ca et 2,1 g de l' par lcg de matière sèche) enrichi en urée mais sans complément minéral. Les pcrtes fécales endogènes de phosphore ont été déterminées par la méthode de dilution isotopique. Le coefficient d'utilisation digestive réelle du phosphore a atteint 7 o p. I oo tandis que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

1980
1980
2003
2003

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
5
2
Order By: Relevance
“…None of these parameters could be recorded in the database. Daily saliva flow (F SAL ) is influenced mainly by DM intake and by dietary fibre content [30] since both affect chewing intensity [5,31]. These factors also affect PSAL (DM intake, model 5 and dietary forage content, model 9).…”
Section: Saliva: the Main Origin Of Faecal Phosphorus Excretionmentioning
confidence: 99%
“…None of these parameters could be recorded in the database. Daily saliva flow (F SAL ) is influenced mainly by DM intake and by dietary fibre content [30] since both affect chewing intensity [5,31]. These factors also affect PSAL (DM intake, model 5 and dietary forage content, model 9).…”
Section: Saliva: the Main Origin Of Faecal Phosphorus Excretionmentioning
confidence: 99%
“…The constant true absorption coefficient values advocated [26,28] appear to be too low. However, the remaining variations are probably due to feedstuffs or diets [6,29,30], differences in phosphorus digestive availability [31] and also differences among species and physiological state.…”
Section: Dietary Phosphorus Availabilitymentioning
confidence: 99%
“…Even though inorganic phosphates have been intensively studied (from 1957 [38] to 1998 [39]), the results are scarce for forages and concentrates. The authors who studied phosphorus digestive availability of forages have reported values of 0.70 [29], of 0.75 [35] and even 0.80 in lactating cows [40] for corn silage. In contrast, true absorption (alfalfa) for hay phosphorus was found to be only 0.55 [41].…”
Section: Dietary Phosphorus Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…They were fed to lambs for the determination of phosphorus requirements [36] and the availability of phosphorus in corn silage [37] and alfalfa hay [17]. Pure forage diets were administered to grazing calves in a study of phosphorus metabolism [22].…”
Section: Experimental Diets (Tab Iv)mentioning
confidence: 99%